Behaviors of self-delivery lidocaine nano systems affected by intermolecular interaction. Issue 12 (23rd January 2023) - Tang, Lei; Qin, Feng; Gong, Deying; Pan, LiLi; Zhou, Changcui; Ling, Rui; Shen, Wenxue; Fan, Qin; Yi, Wenhao; Wu, Fengbo; Wu, Xiaoai; Zhang, Weiyi; et al.
Abstract : Nano systems self-assembled only by lidocaine salts exhibit unexpected unique behaviors in different local tissues based on their intermolecular interaction, and can achieve up to 7.8 h sensory block without excipient residue. Abstract : Lidocaine salts self-assembled into different nano systems in water at a clinical dosage (2%, 0.2 mL) without excipient addition, and led to different sensory block durations and acute systemic toxicities, which were affected by the self-delivery and self-release behaviors of the salts in vivo . These differences were mainly caused by intermolecular π–π stacking under different conditions, which was proved by the unique supramolecular arrangement of gourd-shaped Janus particles. π–π stacking in lidocaine nano systems can be enhanced by carbon dioxide addition or the exchange of counter ions from Br − to Cl − . Without π–π stacking, nano systems self-assembled by lidocaine hydrobromide achieved 7.8 h sensory block by intradermal administration on rats, which is much longer than the efficacy of classical local anesthetics and more suitable for postoperative treatment.